Desain Prototype Sistem Starting Delta Wye Untuk Motor Induksi 3 Phasa Berbasis Laboratorium - Suryani Suryani; Marufah Marufah (Prosiding Seminar Nasional Ilmu Teknik, 2024)
Electric motors with an electromagnetic devices that convert electrical energy into mechanical energy, so it can be that electric motors are include in the category of dynamic electric machines. The research to find out the design of the circuit form protoype from wye delta, how to replace the system control circuit starting wye delta, and obtain a large result measuring the flow current of the 3 phase induction motor when the motor starts the motor running. Method used between another study of literature, than to do design and testing of tools and data retrieval. The results of the system test is effective, obtained, digging, initial current, electric motor with value, with the acquisition of measurement results when using the wye system on R, S, and T phase each 0,6 ampere, 0,8 ampere, and 0,6 ampere. When using the delta system on R phase of 7,5 ampere,S phase of 8,5 ampere, and T phase of 8,3 ampere. Prototype from thid tools operates with controller system, using a toll called a semiautomatic control system, whit an electromagnetic working principle ehere the main function of the contactor is as a magnetic switch.